Writing poems: a waste of time or a savior of life – an autoethnographic exploration. Issue 3 (2nd July 2020) - Sharma, Daneshwar
ABSTRACT: The act of writing poetry in the personal space has therapeutic effects, however, beyond the personal space, is there a utility of poetry? When the society is proclaiming poetry to be dead, the author goes on a soul-searching journey to find out why does he write poems? In his profession as a professor, he has been often asked to write sellable prose, which will also help in his career advancement. The author hovers around these two viewpoints that poetry writing is a wastage of time or a savior of life as he knows it. Despite discouragement from his immediate professional and personal environment, the author continues to record his lived experiences in the form of poetry. Through autobiographical poems and reflections upon them, the author tries to answer this question: Why write poems when nobody is there to publish or read them?